The Roman army in Central Portugal: Reassessing the archaeological evidence of two possible military sites - Gil Vilarinho; Alexandre Jorge Canha; João Fonte (Conimbriga, 2024)
Following a complementary non-invasive analysis including satellite and aerial imagery, as well as UAV-based photogrammetric and LiDAR surveys, this paper presents and discusses the Roman military evidence identified at Alto do Golado (São Pedro do Sul) and Modedufe (Lamego). Though the archaeological remains of these sites have been partly noticed before, undetected relevant aspects resulted in misinterpretations, which are now reassessed in this study. Constituting the first known evidence of the Roman army in the region located between the Vouga and Douro rivers, further analysis of computed GIS models resulted in some hypotheses regarding mobility, visibility and territorial control. Ultimately, this paper also stresses the importance and the need for additional, invasive archaeological research to validate these hypotheses and, consequently, contribute to a better understanding not only of the sites here discussed but also of the Roman military presence in Western Iberia.